'Joy is resistance': cross-platform resilience and (re)invention of Black oral culture online. Issue 6 (12th May 2019) - Lu, Jessica H.; Steele, Catherine Knight
ABSTRACT: Existing research has affirmed that Black people historically mastered oral communication strategies to resist subjugation and oppression by dominant groups, and have emerged as leaders in technological innovation. This article takes seriously Black users' social media engagement and focuses particularly on Black joy online. We analyze a rich collection of discourse spanning both Twitter and Vine through which Black users utilize the affordances of both platforms to challenge dominant narratives that demean and dehumanize Black people. We argue that Black users seize upon the interplay of the applications to not only express and foster joy, but to extend historic legacies of Black oral culture and further cultivate contemporary strategies that leverage – but also transcend – the affordances of each platform.